A sixth-order parabolic equation describing continuum evolution of film free surface - Xiaopeng Zhao (Electronic Journal of Differential Equations, 2014)
In this article, we study the regularity of solutions for a sixth-order parabolic equation. Based on the Schauder type estimates and Campanato spaces, we prove the existence of classical global solutions.